2002
DOI: 10.2166/wst.2002.0072
|View full text |Cite
|
Sign up to set email alerts
|

Particle transport in a karst aquifer: natural and artificial tracer experiments with bacteria, bacteriophages and microspheres

Abstract: Fast changes in spring water quality in karst areas are a major concern for production of drinking water and require detailed knowledge of the complex interaction between karst aquifer, transport behavior of microorganisms and water treatment. We have conducted artificial and natural particle transport experiments at a karst spring with bacteria, bacteriophages, microspheres, and pathogens. Transport of the investigated microorganisms, turbid matter and chemical pullutants as well as increase in discharge are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 0 publications
3
55
0
1
Order By: Relevance
“…A prerequisite for the application of a physical tracer is that it does not destroy the culturability of microorganisms in bioaerosol suspensions and in aerosol state. Uranine, a physical fluorescent tracer, has been reported to be virus-friendly and is detectable in tiny doses (Auckenthaler et al 2002;Ijaz et al 1985a, b). The effect of uranine on bacterial culturability has not been studied extensively, however, and must be assessed for species for which no data are available.…”
Section: Introductionmentioning
confidence: 99%
“…A prerequisite for the application of a physical tracer is that it does not destroy the culturability of microorganisms in bioaerosol suspensions and in aerosol state. Uranine, a physical fluorescent tracer, has been reported to be virus-friendly and is detectable in tiny doses (Auckenthaler et al 2002;Ijaz et al 1985a, b). The effect of uranine on bacterial culturability has not been studied extensively, however, and must be assessed for species for which no data are available.…”
Section: Introductionmentioning
confidence: 99%
“…This may cause critical processes such as preferential flow, which permit contaminants to by-pass deposits that may otherwise attenuate them (Foppen and Schijven 2006). Such processes have been demonstrated to be fundamental in influencing groundwater quality in highly heterogeneous karst aquifers, as indicated by the rapid occurrence of coliforms at karst springs following rainfall events in many studies (Personné et al 1998;Auckenthaler et al 2002;Shevenell and McCarthy 2002;Pronk et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have identified the benefits of employing particulate tracers instead of solutes for assessing the risk of particulate contamination impacting groundwater quality in a range of hydrogeological environments (including karst), where fluorescent microspheres have been widely used as surrogates for bacteria (Harvey et al 1989;Harvey and Harms 2002;Auckenthaler et al 2002) and protozoa (Renken et al 2005) of comparable size. However, although particle size is frequently the dominant criterion considered in microsphere selection, conclusive evidence of their suitability has rarely been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…These phages can be easily produced in large quantities (e.g., 10 15 phages in 10 L) but detected at extremely low levels (∼1 phage in 2 mL); furthermore, they are not harmful to humans and the aquatic environment. Phages are particularly useful to simulate transport and attenuation processes in saturated and un-saturated porous media, either by means of column or batch experiments in the laboratory (8,9) or field experiments in sand and gravel aquifers (10)(11)(12)(13)(14), flowing surface waters (12), waste stabilization ponds (15), or constructed wetland areas (16). Naturally occurring phages that infect fecal or patho-genic bacteria are increasingly used as contamination indicators (17).…”
mentioning
confidence: 99%